Strategi Pengembangan Agrowisata Show Window Di Kelurahan Kakaskasen II Kecamatan Tomohon Utara - Mellese, Agnes Wilda; Talumingan, Celcius; Sondakh, Mex Frans Lodwyk (AGRI-SOSIOEKONOMI, 2023)
The purpose of this study was to describe the Show Window agro-tourism development strategy in Kakaskasen II Village, North Tomohon District. This research was conducted from May to July 2023. The sampling method used purposive sampling and accidental sampling. The data used are primary data and secondary data. Primary data were obtained directly from respondents by conducting direct interviews using questionnaires, to the Secretary of the Tourism Office, Head of the Agriculture Service, Head of Show Window Agro-tourism Center and Employees, Village Staff, Community, and Visitors to Show Window agro-tourism. Secondary data were obtained from related agencies, namely through the Agriculture and Fisheries Service of the City of Tomohon and through the Center for Hatchery, Nurseries and Tourism Agrovidya as well as through literature studies related to the data needed in this study. The analytical method used in this research is SWOT analysis. The results showed that the Show Window Agrotourism Development Strategy in Kakaskasen II Village, North Tomohon District is at the coordinates of 1.06;2.59 which are in quadrant I, which means that this position supports growth strategy (growth).